Sedimentology and Geochemistry of the Upper Permian Linghao Formation Marine Shale, Central Nanpanjiang Basin, SW China - Gu, Yifan; Hu, Dongfeng; Wei, Zhihong; Liu, Ruobing; Hao, Jingyu; Han, Jing; Fan, Zhiwei; Jiang, Yuqiang; Wang, Yansong; Xu, Qidi (Frontiers in Earth Science, 2022)
The Upper Permian Linghao Formation marine shale and contemporaneous transitional shale are the most potential shale gas targets in Nanpanjiang Basin, which is characterized by high TOC value, wide distribution, and large cumulative thickness. Based on division of Linghao Formation, petrographic, mineralogical, high-resolution geochemical analyses were intergrated to reveal sedimentary environment including detrital influx, paleoclimate, paleosalinity, paleoredox conditions and paleoproductivity. There are two organic-rich shale intervals in Linghao Formation, which are Ling 1 Member and lower Ling 3 Member. The lower Ling 1 is dominated by deep-water shelf facies, which is characterized by high TOC value (0.93%-6.36%, avg. 2.43%), high detrital influx proxies (Zr, 746ppm-1508ppm, avg. 1093ppm; Ti, 19278ppm-128730ppm, avg. 16091ppm), relatively warm-humid paleoclimate condition (CIA*, 75.94-91.90, avg. 82.26), low paleosalinity proxies (Sr/Ba, 0.13-0.34, avg. 0.22), and high paleoproductivity (P/Al (10-2), 1.06-2.06, avg. 1.63; Mn/Ca (10-3), 27.37-291.69, avg. 128.07). Detrital influx including gravity flow plays a critical role for enrichment of organic matter. The sedimentary enviroment of upper Ling 1 and lower Ling 3 is same as lower Ling 1. Unlike lower Ling 1, these intervals are characterized by low detrital influx proxies, moderate weathering, and relatively high paleosalinity proxies. The volcanic ash of Emei volcanism and felsic volcanism in South China play the critical role for enrichment of organic matter in upper Ling 1 and lower Ling 3, respectively. The sedimentary models for Linghao Formation organic-rich shale can reveal factors controlling the enrichment of organic matter.